Correction to: Running on a high: parkrun and personal well-being - Anne Grunseit; Justin Richards; Dafna Merom (BMC, 2019)
It was highlighted that the original article [1] contained an error in the proportions reported in the Results, at the Representativeness of registered parkrunners section.